Competition or Cooperation? : Using Team and Tournament Incentives for Learning among Female Farmers in Rural Uganda - Vasilaky, Kathryn N.; Islam, Asif M. (Elsevier, 2018)
This study explores the behavioral learning characteristics of smallholder female farmers in Uganda by quantifying the amount of information learned under different incentive schemes. The paper shows how competitive versus team incentives compare in motivating Ugandan farmers to learn and share information relevant to adopting a new agricultural technology. We find that tournament-based incentives provide greater outcomes in terms of total information learned than threshold-based team incentives. Furthermore the order of the incentive – whether the tournament precedes or follows the team incentive scheme – does not affect the volume of information learned. New information introduced between rounds was learned by more individuals under team incentives than under tournament incentives. The study provides direct practical policy recommendations for improving learning in the context of agriculture in Uganda.